2019
DOI: 10.1080/14786419.2018.1543673
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cytoprotective effects of compounds isolated from Copaifera langsdorffii Desf. against induced cytotoxicity by exposure to methylmercury and lead

Abstract: Copaifera langsdorffii L. is one of the most known medicinal species in Brazil. Its leaves are rich in phenolic compounds with potential biological activities as an antioxidant and chelating agent. This paper reports the isolation of four compounds from the hydroalcoholic extract of the leaves of C. langsdorffii and the investigation of their possible cytoprotective effects against heavy metal poisoning. Quercitrin (1), afzelin (2), 3,5-di-O-(3-O-methyl galloyl) quinic acid (3) and 4,5-di-O-(3-O-methyl galloyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Similarly, treatment with C. paupera (B) provided survival percentages higher than 75% ( Figure 3 ). Previously, we had reported the absence of genotoxic effects on the micronucleus frequencies of Chinese hamster lung fibroblast (V79) cell cultures and even a cytoprotective effect of Copaifera spp leaf extracts, which we associated with the large number of phenolic compounds in the extracts [ 5 , 46 ]. All these data indicated the efficacy and safe use of Copaifera leaf extracts against C. glabrata infection.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, treatment with C. paupera (B) provided survival percentages higher than 75% ( Figure 3 ). Previously, we had reported the absence of genotoxic effects on the micronucleus frequencies of Chinese hamster lung fibroblast (V79) cell cultures and even a cytoprotective effect of Copaifera spp leaf extracts, which we associated with the large number of phenolic compounds in the extracts [ 5 , 46 ]. All these data indicated the efficacy and safe use of Copaifera leaf extracts against C. glabrata infection.…”
Section: Resultsmentioning
confidence: 99%
“…Antiviral Activity [37] Neuraminidase inhibition: IC 50 = 311.76 µM (Oseltamivir acid IC 50 = 280 µM). Myeloperoxidase inhibition [38] IC 50 = 2.0 ± 0.2 µM Prevention of metal toxicity effects [39] Almost 100% HepG2 cell line viability when treated with 1 µM + 15 µM MeHg (50% viability when only treated with 15 µM MeHg). Almost 100% HepG2 cell line viability when treated with 1 µM + 40 µM Pb(NO 3 ) 2 (50% viability when only treated with 40 µM Pb(NO 3 ) 2 ).…”
Section: In Vitro Activitiesmentioning
confidence: 99%
“…Mercury and lead are considered as threats to human organisms, due to their low elimination rate and high accumulation, which have nefarious effects in several physiological functions, especially of liver and nervous system [67,68]. A study carried out by Aldana et al [39] demonstrated the capacity of quercitrin (9) as cytoprotective agent for the HepG2 cell line against both metals. However, on PC12 cells, quercitrin was only able to protect against the effects of lead [39].…”
Section: D-glcpymentioning
confidence: 99%
See 2 more Smart Citations